Reduction of Active Power Loss at 110/220 kV Node Substations Using Fuzzy Controller - Krysanov V.N.; Burkovsky V.L.; Danilov A.D. (Problems of the Regional Energetics)
One of the most important informational components of control systems is the data of the static load characteristics of each transformer of the substation. Currently, the evaluation of real static characteristics of the load is determined generally by the following methods: computational, ana-lytical, passive and active experiments. These methods exhibit significant disadvantages regarding accuracy and cost rating and encounter plenty of parameters that are difficult to formalize (including climatic factors). The purpose of this work is to reduce electric power losses at 110/220 kV substations by implementation of a new control system for power transformers. This goal has been achieved by using a fuzzy controller in the structure of the control system for power transformers of 110/220 kV tie substations. The presented solution is multi-functional and can be extended to a wide class of power facilities. The results of the simulation of the transformer voltage regulation process, performed in the MatLAB application environment, showed that the implementation of a new fuzzy controller structure had improved the efficiency of the substation power control system in forecasting and management (compared to classical solutions based on regression and probabilistic models). Herewith, the most accurate accounting of consumer load, the maximum use of equipment at the substation for voltage regulation at the points of release and a significant reduction of active power losses at the tie substa-tions 110/220 kV (up to 12,12%) compared to already known solutions were observed.